PENAMAAN PROGRAM STUDI DAN GELAR PADA PENDIDIKAN TINGGI ILMUPERPUSTAKAAN DI INDONESIA - Yunus Winoto (Perpustakaan Nasional RI, 2019)
The naming of studies programs and degrees for library graduates in indonesia higher education still variens. Thus with the issuance of the new regulation, which is the ministry of research and technology’s regulation No. 15 of 2017 and the ministry of the research and technology ministerial decree no. 257 of 2017 abaout the naming of studies programs and degrees of higher eduction in Indonesia, will have a significant impect on improvingthe name of studies progras in Indonesia higher education, including library studies program. The existence of this new regulation, ecspeciallyfor library, museum and archival education, ensures clarity about the clump of science that is in the clump of information science. Therefore, the issuance of the regulation ( the Ministry of Research and Tehcnology’s Regulation No.15 of 2015) Needs to be addressed immediately because every higher education is obliged to adjust the name of their studies progrms in accordance with the nomenclature no later than one (1) after the regulation is issued.